(untitled) (Journal of Philosophy Culture and Political Science, 2018)
In this article we will look at one of the large-scale problems of the modern world community – Islamophobia. The problem, which was the result of political games, unreliability of information and competent approach the world media when considering a particular situation involving «Muslim» radicals. The emergence of Islamophobia accompanied by a variety of factors, ranging from terrorist attacks committed martyrs in different countries and the collapse of the twin towers on Sept. 11, 2001, a group of people to attack the French edition of Charlie Hebdo and the emergence of Islamic State of Iraq and the Levant, remembering all these things, just recently on 13 November 2015 in Paris, there was another terrorist attack. But, nevertheless, there is one link among the political and terrorist acts – crimes committed by members of radical groups under the banner of Islam. Key words: ISIS, Islam, Radicalism, Extremism, Stereotypes, Charlie Hebdo, The Quran.